Water Quality Analysis and Evaluation of Five Rivers in Poyang Lake Based on Three Water Quality Index Methods - YE Fangqi; JI Yong; HUI Yuan; ZHANG Chenhui; CHENG Yuxiang (Renmin Zhujiang)
To study the pollution status of the five water systems of Poyang Lake, this paper analyzes and evaluates the water quality of the Ganjiang River, Xinjiang River, Fuhe River, Xiuhe River, and Raohe River by adopting the gray correlation method, the single-factor evaluation method and the comprehensive pollution index evaluation method. Five evaluation factors, namely, dissolved oxygen, potassium permanganate, ammonia nitrogen, total nitrogen, and total phosphorus are selected. The results show that the overall water quality of the studied waters is between Class I and Class III, with all five rivers showing excessive total nitrogen levels throughout the year due to agricultural wastewater discharge, and low dissolved oxygen levels in July and August due to high temperatures. By using the gray correlation method, single factor evaluation method, and integrated pollution index evaluation method, the study analyzes the advantages and disadvantages of the three methods, and compares and synthesizes the evaluation results. Specifically, the integrated pollution index method and the gray correlation method provide more objective results, and the results of the study can be used as a reference for the prevention and control of water pollution in the "Five Rivers" as well as for the integrated management of water quality.